PEMBINAAN KANTIN KAMPUS MELALUI HIGIENE PENJAMAH MAKANAN - Laras Sitoayu; Putri Ronitawati; Vitria Melani; Nazhif Gifari (DHARMA RAFLESIA, 2020)
The Canteen is a facility that is often visited by many people, therefore the canteen cleanliness and health need attention. Especially The canteen in places such as education providers. Whatever is served by canteen will be consumed by campus residents and become a daily habit to consume it. Contamination that occurs in the canteen will endanger campus residents, and if consumed by many people will cause many victims. This will certainly endanger the health of campus residents, especially students and employees. Food handler’s personal hygiene and completeness of APD are closely related to food contamination. For this reason, it is necessary to develop a healthy canteen, one of which is by providing education about personal hygiene and the importance of using APD when food is personalized. This activity is a community service of the Nutrition Study Program Faculty of Health Sciences (FIKes)Esa Unggul University. The purpose of this activity is to create a healthy and pollution free canteen Esa Unggul University. All food handlers canteen attended and participated in this activity well. Activities like this are important to carry out to cultivate a healthy canteen in an educational environment such as a campus.